Analysis of Investment Feasibility in The Construction Project of Intan Hotel Masohi City, Central Maluku Regency - Julez Franco Lekatompessy; Felix Taihuttu; Christy Gery Buyang; Mansye Ronal Ayal (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The construction of the Intan Hotel in Masohi City, Central Maluku Regency is one of the strategic efforts to support the growth of the tourism sector and improve the regional economy. As government, economic activity, and tourist visits in Masohi City increase, the need for adequate accommodation facilities has become increasingly important. However, the amount of funds needed in the construction of hotels requires an investment feasibility analysis so that the project can provide optimal financial benefits and minimize the risk of losses in the future. This study aims to analyze the feasibility of investment in the Masohi City Intan Hotel Development Project from a financial aspect. The research method used is a quantitative approach with Net Present Value (NPV), Benefit Cost Ratio (BCR), and Payback Period (PP) analysis methods. The data used consisted of primary data obtained through direct observation at the research site, interviews with related parties, and surveys, and secondary data in the form of Cost Budget Plan (RAB), banking interest rates, and investment age. The analysis was carried out taking into account the investment life of 10 years and the prevailing average bank interest rate. In addition, this study also uses several Room Occupancy Rate (TPK) scenarios, namely high, normal, low, and actual scenarios, to describe different hotel operational conditions. The results of the study show that in all scenarios analyzed, the Net Present Value (NPV) value is positive, the Benefit Cost Ratio (BCR) is greater than one, and the Payback Period (PP) is smaller than the set investment life. This shows that the Masohi City Intan Hotel construction project is financially feasible to be implemented and developed. This investment is expected to be able to provide sustainable profits and contribute to the development of the hotel sector and the economy of the Central Maluku Regency.